Modeling of Threshold Voltage and Drain Current of Uniaxial Strained p-MOSFETs - Amit Chaudhry; Sonu Sangwan; Jatindra Nath Roy (Журнал нано- та електронної фізики)
An analytical model describing the threshold voltage and drain current in strained-Si p-MOSFETs as a function of applied uniaxial strain applied at the gate has been developed in this paper. The uniaxial stress has been applied through the silicon nitride cap layer. The results show that the threshold voltage falls and drain current rises due to applied uniaxial strain. The results have also been compared with the experimentally reported results and show good agreement.